Antioxidant, Anti-inflammatory and Xanthine oxidase inhibitory Activity of Tephrosia purpurea Plant Extracts - Shivraj Hariram Nile; Arti Baburao Mahajan; C.N. Khobragade; Se Won Park (International Journal of Phytomedicine, 2012)
T. purpurea whole plant extract (TPWPE) was evaluated for antioxidant, anti-inflammatory, and xanthine oxidase (XO) inhibitory activities. Antioxidant activity was measured using ABTS and FRAP methods, anti-inflammatory activity was measured by Diene-conjugate and β-glucuronidase assay. In vitro XO inhibitory activity was measured by using cow milk xanthine oxidase enzyme. The average antioxidant activity of TPWPE (1-2 µg/mL) in the reacting system revealed significant activity viz; 42.2 (ABTS) and 36.5 (FRAP) percent. The anti-inflammatory activities reveled, 45.40 and 70.50 percent inhibition. The result for XO inhibitory activity by plant extracts reveled, 95.5 % inhibition to that, off control (allopurinol) 92 % inhibition. The kinetic parameters of XO inhibition, revealed noncompetitive mode of inhibition, where, Km and Vmax of TPWPE extracts (25 to 100 µg/mL)) were, 0.25 mM/mL and 0.040, 0.036, 0.032 and 0.030 (µg/min) while for positive control Km and Vmax is 0.30 mM/mL and 0.045 (µg/min) respectively. Results suggest that, TPWPE can be exploited against diseases associated, with free radical formation and xanthine oxidase activity; further by isolation and structural elucidation of active phytochemicals from TPWPE.